Post-coating treatment effects on the physicomechanical and corrosion resistance of plasma-sprayed hydroxyapatite (FSHA) on TI-13NB-13ZR alloy for biomedical applications - Che Nor Aiza Jaafar (Tanjung Malim, 2021)
Post-coating treatment effects on the physicomechanical and corrosion resistance of plasma-sprayed hydroxyapatite (FSHA) on TI-13NB-13ZR alloy for biomedical applications by Che Nor Aiza Jaafar